TRADE LIBERALIZATION AND ITS EFFECTS ON SUGAR TABLE INDUSTRY, WELFARE, AND ECONOMY: A CASE OF INDONESIA - Muhamad, Gunawan; Nugroho, Ario Seno (Politeknik Keuangan Negara STAN)
ABSTRACT: This paper examines the effects of trade liberalization on the sugar industry, the consumer welfare, and the whole economy in Indonesia using a computable general equilibrium model based on 2008 Indonesia Input-Output Table. The common argument concerning the effects of trade liberalization is that consumers benefit from trade liberalization while domestic industries suffer from that. However, this paper found that both the consumers and the domestic industries suffer from trade liberalization scenario. The smaller the tariff rate, even if the subsidy rate was applied, the lower the welfare and the utility. The more decrease in the consumer’s welfare and in the utility would be suffered when the trade liberalization scenario was financed by increasing the production tax rate or the income rate. Finally, when the tariff rate was increased and assumed that the government consumption would adjust, the consumer’s welfare, the utility and the overall producer’s income would increase. Even though, the domestic producer in the sugarcane and sugar refinery industry would suffer. Finally, manufacturing sector seems has the highest benefit from trade liberalization while in the agriculture sector is estimated has a minor outcome. Key Words: Trade Liberalization, Computable General Equilibrium (CGE), Sugar, Welfare, UtilityABSTRACT: Makalah ini membahas dampak liberalisasi perdagangan terhadap industri gula, kesejahteraan konsumen, dan keseluruhan ekonomi di Indonesia dengan menggunakan computable general equilibrium model yang dihitung berdasarkan Tabel Input-Output Indonesia tahun 2008. Perdebatan umum mengenai efek dari liberalisasi perdagangan adalah bahwa konsumen mendapat manfaat dari liberalisasi perdagangan sementara industri dalam negeri menderita dari perdagangan bebas. Namun, dari hasil penelitian ini, peneliti menemukan bahwa konsumen dan industri domestik, sama-sama menderita dari skenario liberalisasi perdagangan. Semakin kecil tingkat tarif, meskipun dengan pemberian subsidi oleh pemerintah, maka semakin rendah tingkat kesejahteraan konsumen dan utilitas. Penurunan kesejahteraan konsumen dan utilitas yang lebih besar akan diderita ketika skenario liberalisasi perdagangan dibiayai dengan menaikkan tarif pajak produksi atau tarif pajak penghasilan. Akhirnya, ketika tingkat tarif meningkat dan diasumsikan bahwa konsumsi pemerintah akan disesuaikan, kesejahteraan konsumen, utilitas dan pendapatan produsen secara keseluruhan akan meningkat. Meski demikian, produsen dalam negeri di industri tebu dan gula rafinasi akan menderita. Akhirnya, sektor manufaktur diperkirakan mendapat manfaat tertinggi dari liberalisasi perdagangan, sedangkan di sektor pertanian, diperkirakan mendapat manfaat yang rendah.Kata kunci: Liberalisasi Perdagangan, Computable General Equilibrium (CGE) Gula, Kesejahteraan, Utilitas